Correction: Preliminary Validation of a High Docosahexaenoic Acid (DHA) and α-Linolenic Acid (ALA) Dietary Oil Blend: Tissue Fatty Acid Composition and Liver Proteome Response in Atlantic Salmon (Salmo salar) Smolts. - PLOS ONE Staff (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0161513.].